Gut microbiota: a potential influencer of insomnia occurring after COVID-19 infection - Fang, Jiale; Wang, Siwen; Liu, Lijia; Zhang, Xiaoyi; Liu, Ruilong; Pang, Xingchao; Cui, Jiankun; Han, Jianshu; Zhu, Xinyu (Frontiers in Psychiatry, 2024)
The prevalence of insomnia has increased in recent years, significantly affecting the lives of many individuals. Coronavirus disease 2019 (COVID-19) infection has been found to have a substantial impact on the human gut microbiota (GM). Clinical studies have shown that the high prevalence, prolonged duration, and refractory treatment of insomnia symptoms following the COVID-19 pandemic may be related to the effect of COVID-19 infection on the GM. Therefore, the GM may be a potential target for the treatment of insomnia following COVID-19 infection. However, relevant studies have not been well-documented, and the GM has not been sufficiently analyzed in the context of insomnia treatment. Herein, we review the interaction between sleep and the GM, summarize the characteristics of COVID-19-induced abnormal changes in the GM and metabolites in patients with insomnia, and discuss potential mechanisms, including metabolic, immune, and neural pathways, by which these abnormal changes in the GM cause insomnia as well as the factors affecting the GM. Finally, we discuss 1 Abbreviations: gut microbiota (GM); coronavirus disease 2019 (COVID-19); severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); post-acute COVID-19 syndrome (PACS); Firmicutes/Bacteroidetes (F/B); traditional Chinese medicine (TCM); fecal microbiota transplantation (FMT); angiotensin-converting enzyme 2 (ACE-2); short-chain fatty acids (SCFAs); 5-hydroxytryptophan (5-HT); weight loss (WL); tea polyphenols (TPs); microbiota-gut-brain axis (MGBA); gamma-aminobutyric acid (GABA); vagus nerve (VN); non-rapid eye movement (NREM); tumor necrosis factor alpha (TNF-α); rapid eye movement (REM); Pittsburgh Sleep Quality Index (PSQI); fructooligosaccharides (FOSs); galactooligosaccharides (GOSs); p-chlorophenylalanine (PCPA); mongolian medical warm acupuncture (MMWA). the prospect of modulating the host GM community for the effective treatment of insomnia after COVID-19 infection and the need for further clinical studies.